Variations in leptin, nesfatin-1 and irisin levels induced by aerobic exercise in young trained and untrained male subjects - Sermin Algul; Cagri Ozdenk; Oguz Ozcelik (Termedia Publishing House, 2017)
The aims of this study were to investigate the impacts of acute aerobic exercise on circulating levels of hormones associated with energy metabolism, namely leptin, nesfatin-1 and irisin, in trained and untrained male subjects and to determine whether the timing of the exercise (i.e. morning or night) amplified these impacts. Thirty trained (19.2±0.7 years) and 30 untrained (19.5±0.6 years) male subjects performed two aerobic running exercises (3 days between tests) to 64-76% of the subjects' maximal heart rate for about 30 min. Pre- and post-exercise venous blood samples were taken and analysed for leptin, nesfatin-1 and irisin using enzyme-linked immunosorbent assay (ELISA). Paired samples and independent samples t-tests were used to analyse data. Irisin levels increased in all the subjects (p<0.001). In both groups, nesfatin-1 levels increased significantly after the night-time exercise (p<0.05). Importantly, leptin and nesfatin-1 levels varied among the trained and untrained groups: Both leptin and nesfatin-1 levels increased in 4 (13%) and 12 (40%) subjects, respectively, after the morning exercises, and they increased in 9 (30%) and 10 (33%) subjects, respectively, after the night-time exercise. They decreased in 5 (16%) and 7 (23%) subjects, respectively, after the morning exercise and in 6 (20%) and 3 (10%) subjects, respectively, after the night-time exercise. Exercise may result in increased energy consumption by altering irisin levels. However, due to variations among individuals, increasing leptin and nesfatin-1 levels by reducing food intake may not be applicable.